Health, responsibility and taxation with a fresh start - Aitor Calo-Blanco (SERIEs - Journal of the Spanish Economic Association, 2017)
In a model where individuals differ in both their health care needs and their lifestyle preferences, we examine the fair provision of health care when those who regret their initial decisions are granted a fresh start. By considering that each agent chooses how to allocate a given amount of resources between medical and non-medical consumption, we characterise the scheme of taxes and health treatments that maximises social preferences. These preferences allow the planner to make welfare assessments when it is acceptable to compensate agents who have changed their preferences and/or who are endowed with a bad medical disposition. We show that the optimal tax scheme does not only pay additional treatments for those who are not in a good health state, but also protectively induces agents to reduce their non-medical consumption in order to limit a possible future regret.
Keywords: D63; D71; H20; I10; 330; Health; Lifestyle preferences; Fairness; Fresh start; Taxation